29‐4: PI‐less IPS/FFS Liquid Crystal Displays Utilizing Reactive LC with Cinnamate Moiety. Issue 1 (30th May 2018) - He, Rui; Wen, Pushan; Lee, Chang Suk; Kim, Yulki; Kang, Shin-Woong; Lee, Seung Hee; Lee, Myong-Hoon
Abstract : Uniaxial alignment of LC molecules is achieved by irradiating polarized UV at clearing temperature to the mixture of LC and new reactive mesogen having cinnamate moiety without using any conventional alignment layer. The IPS/FFS cell fabricated by the proposed technology showed excellent electro‐optic characteristics and robust reliability, which could contribute to the low‐cost and green LCDs.